2022
DOI: 10.1186/s13063-022-06765-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of health education intervention on demand of women for cervical cancer screening: a cluster-randomized controlled trial

Abstract: Background Cervical cancer is considered preventable disease, though it is the second largest killer of women’s cancer in low and middle-income countries. Despite the government’s attempts to broaden screening facilities, the screening service utilization was poor. Our study evaluated the impact of health education intervention on women’s demand for cervical cancer screening. Methods Community-based cluster-randomized controlled trial was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Regarding total knowledge, the satisfactory level of the total knowledge scores was increased from 34% in the pre-test to 86% in the post-test. This improvement was maintained during the follow-up assessment, with 77.3% of participants still demonstrating a satisfactory level of knowledge with statistically significant differences (P<0.001) these results were in agreement with several previous studies (Abera et al, 2022;Amin et al, 2021;Alkalash et al, 2020;Kazemi et al, 2022;Sonawane & G Mendagudli, 2020;Rosyda et al, 2019)…”
Section: Concerningsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding total knowledge, the satisfactory level of the total knowledge scores was increased from 34% in the pre-test to 86% in the post-test. This improvement was maintained during the follow-up assessment, with 77.3% of participants still demonstrating a satisfactory level of knowledge with statistically significant differences (P<0.001) these results were in agreement with several previous studies (Abera et al, 2022;Amin et al, 2021;Alkalash et al, 2020;Kazemi et al, 2022;Sonawane & G Mendagudli, 2020;Rosyda et al, 2019)…”
Section: Concerningsupporting
confidence: 92%
“…However, these findings exceeded those of a randomized trial examining the impact of an educational intervention on women's demand for cervical cancer screening. , Abera et al, (2022) found that after follow-up, the readiness for cervical cancer screening in the intervention group had increased by 46.4%. Additionally, Almutairi et al, (2022) revealed that the awareness and knowledge regarding Pap smear after the education session improved significantly by 1.5-3 times increase (p=0.000).…”
Section: Concerningmentioning
confidence: 95%
“…This underscores the importance of health education in fostering women's participation in screening initiatives. [24][25][26] Nevertheless, notably, women in underdeveloped areas, particularly older women, may not have received systematic education, face challenges in reading and writing, or may have limited access to useful information via mobile phones. Additionally, owing to their geographical distance, they may encounter di culties in accessing public health services.…”
Section: Discussionmentioning
confidence: 99%
“…Desse modo, se faz necessário a realização de ações educativas pelos os profissionais da saúde utilizando várias estratégias como: palestras orientando como se prevenir do câncer do colo do útero , visitas e interação ao autocuidado e prevenção nos estabelecimentos de acesso a saúde, também em outros estabelecimentos como empresas as quais as mulheres trabalham incentivando as mulheres a realizarem o exame preventivo, e dessa forma sanar e desmistificar as crenças prejudiciais para a prevenção em saúde (Dalazoana et al, 2020;Abu et al, 2020;Abera et al, 2022).…”
Section: Discussionunclassified

Cervical Cancer

Darlly Vieira Dos Santos,
Erika Abrantes Coutinho,
Caroline de Souza
et al. 2023
hs